Fisher information, delocalization and the semiclassical description of molecular rotation - Curilef, S. (2007)
We discuss phase-space delocalization for the rigid rotor within a semiclassical context by recourse to the Husimi distributions of both the linear and the 3D-anisotropic instances. The Husimi function can be viewed in a variety of ways. In particular, we obtain it as the expectation value of the density operator in a suitable basis of coherent states. Our treatment is based upon the concomitant Fisher information measures. The pertinent Wehrl entropy is also investigated in the linear case.